Assessment of the Oxidative Potential and Oxidative Burden from Occupational Exposures to Particulate Matter. Issue 3 (1st October 2021) - Fleck, Alan da Silveira; Debia, Maximilien; Ryan, Patrick Eddy; Couture, Caroline; Traub, Alison; Evans, Greg J; Suarthana, Eva; Smargiassi, Audrey
Abstract: Oxidative potential (OP) is a toxicologically relevant metric that integrates features like mass concentration and chemical composition of particulate matter (PM). Although it has been extensively explored as a metric for the characterization of environmental particles, this is still an underexplored application in the occupational field. This study aimed to estimate the OP of particles in two occupational settings from a construction trades school. This characterization also includes the comparison between activities, sampling strategies, and size fractions. Particulate mass concentrations (PM4-Personal, PM4-Area, and PM2.5-Area ) and number concentrations were measured during three weeks of welding and construction/bricklaying activities. The OP was assessed by the ascorbate assay (OP AA ) using a synthetic respiratory tract lining fluid (RTLF), while the oxidative burden (OB AA ) was determined by multiplying the OP AA values with PM concentrations. Median (25 th –75 th percentiles) of PM mass and number concentrations were 900 (672–1730) µg m –3 and 128 000 (78 000–169 000) particles cm –3 for welding, and 432 (345–530) µg m –3 and 2800 (1700–4400) particles cm –3 for construction. Welding particles, especially from the first week of activities, were also associated with higher redox activity (OP AA : 3.3 (2.3–4.6) ρmol min –1 µg –1 ; OB AA : 1750 (893–4560) ρmol min –1 m –3 ) compared to the construction site (OP AA : 1.4 (1.0–1.8) ρmol min –1 µg –1 ; OB AA : 486 (341–695) ρmol min –1 m –3 ). The OP AA was independent of the sampling strategy or size fraction. However, driven by the higher PM concentrations, the OB AA from personal samples was higher compared to area samples in the welding shop, suggesting an influence of the sampling strategy on PM concentrations and OB AA . These results demonstrate that important levels of OP AA can be found in occupational settings, especially during welding activities. Furthermore, the OB AA found in both workplaces largely exceeded the levels found in environmental studies. Therefore, measures of OP and OB could be further explored as metrics for exposure assessment to occupational PM, as well as for associations with cardiorespiratory outcomes in future occupational epidemiological studies.